The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1631/jzus.a1500186
|View full text |Cite
|
Sign up to set email alerts
|

On the identification of weather avoidance routes in the terminal maneuvering area of Hong Kong International Airport

Abstract: Abstract:The safety and efficiency of air traffic are significantly affected by adverse weather. This holds especially in terminal maneuvering areas (TMA) where, in addition to the impact of weather itself, potential weather avoidance routes are strongly restricted by air traffic regulations. A weather avoidance model DIVMET has been developed which proposes a route through a field of developing thunderstorms. Air traffic control regulations have not been included in it at this stage. DIVMET was applied to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The smoothing reduces the maxima slightly; for this reason a reduction of the threshold is reasonable. A threshold of 7 mm h −1 is used, which is slightly below the value of 37 dBZ that is mentioned in the literature to affect aviation (Sauer et al ., ).…”
Section: Methodsmentioning
confidence: 92%
See 1 more Smart Citation
“…The smoothing reduces the maxima slightly; for this reason a reduction of the threshold is reasonable. A threshold of 7 mm h −1 is used, which is slightly below the value of 37 dBZ that is mentioned in the literature to affect aviation (Sauer et al ., ).…”
Section: Methodsmentioning
confidence: 92%
“…The value at which reflectivity starts to affect air traffic operations depends on several factors such as the aircraft type; ideally, the definition of a ‘significant’ convective intensity threshold event should reflect the fact that a competent pilot will decide whether or not to divert his/her flight to avoid it. Surveys in the aviation community have demonstrated that pilots tend to avoid regions with radar reflectivities above 37 dBZ, which corresponds to a precipitation intensity of about 7.5 mm h −1 (Sauer et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Weather conditions influence pilots' performances [9], [10]. Tamura et al [11] conducted a simulation study to examine the differences in pilots' scanning behavior during takeoff in daytime and nighttime situations.…”
Section: Introductionmentioning
confidence: 99%